Answer: f(x)=(x+3)^2-13 = (-3|-13)
Step-by-step explanation:
x^2+6x-4
x^2+6x+3^2-3^2-4
(x+3)^2-3^2-4
(x+3)^2-13
what are the properties ?
Line 1: (-7x+3)+2x
Line 2: (3+(-7x))+2x
Line 3: 3+(-7x+2x)
Line 4: 3+(-5x)
Step-by-step explanation:
line number Property
Line 1: (-7x+3)+2x associative (gathering -7x and 3)
Line 2: (3+(-7x))+2x. Commutative (change the positions of 3 and -7x)
Line 3: 3+(-7x+2x). associatI’ve
Line 4: 3+(-5x)
Alguien me puede explicar los binomios en matematica, porfavor :)
Answer: SEE EXPLANATION (en ingles)
Step-by-step explanation:
A binomial is an algebraic expression of the sum or the difference of two terms.
En espanol: Un binomio es una expresión algebraica de la suma o la diferencia de dos términos.
Algebra help please!
Answer: I am very sorry, but I don't know the answer either
Please answer correctly !!!!!!!!! Will mark brainliest !!!!!!!!!!!!!
Answer:
Step-by-step explanation:
x^2+4x+4=x²+2x+2x+4
=x(x+2)+2(x+2)
=(x+2)(x+2)
=(x+2)²
side length=x+2 meters
Which statement is true about the y-intercept of a quadratic function?
A.
A quadratic function can only have one y-intercept.
B.
A quadratic function can have up to two y-intercepts.
C.
The y-intercept is also called a zero of the function.
D.
The y-intercept is located at the point where the value of y is 0.
Reset
Next
Answer:
A.
Step-by-step explanation:
A quadratic function may only intercept the y-axis once. This is because the definition of a y-intercept tells us that it is the point where x = 0. If there are multiple points where x = 0, then the expression cannot be a function. As such, a quadratic function can only have one.
Choice B contradicts the previous statement.
Choice C is wrong because the x-intercept is the zero of the function. This is because at a given x-coordinate that touches the x-axis, the y-coordinate will be 'zero'.
Choice D is wrong because the y-intercept is where x = 0.
I hope this helps!
A recipe instructs the cook to use 4 cups of water for each 3 cups of powder. If you used 10 cups of water, how much powder should be added?
Answer:
it would b 2 in half cups of powder
Originally the dimensions of a rectangle were 15cm by 20cm. When both dimensions were decreased by the same amount, the area of the rectangle is half the area of the original rectangle. Find the dimensions of the new rectangle.
Answer:
Step-by-step explanation:
We can write an equation to represent this problem.
(15 + w)(20 + w) = 1/2 (15)(20)
Foil out the left side of the equation.
300 + 35w + w^2 = 150
Subtract 150 from both sides.
w^2 + 35w + 150 (I rearranged it to be in the form that is most efficient)
Now solve for variable w using the quadratic equation (look up the formula if necessary)
[-35 +_ (square root of the value of 1225-600)] / 2
[-35 +_ (SqRt of 625)] /2
(-35 +_ 25) /2
= -30, -5
I just realized that it can't increase by a negative number, so I'm not really sure of the answer. Sorry, my bad. However, I feel that this may be of help to other people anyway, so I think I'll leave it up here. Apologies again.
Feel free to read through my reasoning behind my answer, and see if it gives you any ideas or inspiration for solving this problem.
[64] {y}^{2} [+4y-3]
Answer:
(16y-3) (4y+1)
Step-by-step explanation:
using quadratic formula i.e.ay^2+by+c=0
64y^2+4y-3
64y^2+16y-12y-3
16y(4y+1)-3(4y+1)
(16y-3) (4y+1)
hope it help yuh...mark brianliest if my answer suit your question.
The length of a rectangle is 4 inches more than its width and its perimeter is 34 inches find the length and width of the rectangle if w= the width of the rectangle then the length equals
Answer:
The length and width of the rectangle are 10.5 in and 6.5 in respectively.
Step-by-step explanation:
P = 2L + 2W
P (perimeter of the rectangle) = 34 in
L (length of the rectangle) = 4 in + W (width of the rectangle)
Therefore, L = 4 + W
P = 2L + 2W
34 = 2(4 + W) + 2W
34 = 8 + 2W + 2W
34 - 8 = 4W
26 = 4W
W = 26/4 = 6.5 in
L = 4 + W = 4 + 6.5 = 10.5 in
L = 10.5 in
W = 6.5 in
To change a recipe that serves 8 to make it serve 5, by what fraction would you multiply each ingredient?
plsss! help me will mark brainlest!
Answer:
Two polygons are similar with factor k.
=> The ratio between the area of two polygons: r = k^2
=> Here, the area of polygon B is larger than polygon A: 5^2 = 25 times
Hope this helps!
:)
Answer:
Area of polygon B is larger than the area of Polygon A by 25 times.
Step-by-step explanation:
The simplest way of finding this would be to draw a rough image of polygon A and B.
Let's say you drew Polygon A and B as rectangles. Since the scale factor is 5, the dimensions of the sides of polygon B would be 5 times as that of the dimensions of polygon A.
if you label the dimensions of Polygon A as length 2cm and width as 1cm, its area would be 2 square centimetres.
now keeping the scale factor of 5 in mind, multiply the length and the width by 5. you will get the length of polygon B as 10cm and width as 5cm. the area of polygon B becomes 50 square centimetres.
once you have done this, you will realise that the area of polygon B is 25 times the area of polygon A.
Hope this helped:)
how to solve triangles using the law of sines?
Answer:?
The following list shows how many brothers and sisters some students have:
2, 4, 3, 3, 4, 2, 4, 3, 3, 2, 3, 4
State the mode.
Step-by-step explanation:
A triangle has the coordinates
A(4, -1), B(3, -3), and C(0, 2).
Reflect the triangle over the y-axis and find the coordinates of its image.
A(4, -1) - AU
B(3,-3) - BO
C(0, 2) - C'e
-od
Answer:
coordinates of its image
A' = ( -4, -1)
B' =( -3, -3)
C' = ( 0, 2)
Step-by-step explanation:
Reflect in y-axis means mirror it's points in the y -axis.
This means that the x coordinate of each point, changes only. Any mirrored point in the y-axis, will change only, by multiplying the x-coordinate by -1.
(Remember, zero multiplied by -1 remains 0).
Given are these points A, B, and C.
A = (4, -1)
B = (3,-3)
C = (0, 2)
After mirroring in the y- axis you get:
A' = ( -4, -1)
B' =( -3, -3)
C' = ( 0, 2)
what is the exponential regression equation that fits these data
Answer:
picture
Step-by-step explanation:
Helpppp ASAP helpppp
Answer:
a)
side a is opposite, side b is adjacent, side c is hypotenuse
b)
side a is adjacent, side b is opposite, side c is hypotenuse
Step-by-step explanation:
Answer:
Hhhhhhh
Step-by-step explanation:
Huhhhhhgg
i’m so confused! i tried to watch a video on it but i don’t understand and we need to do work :(
the 9. is 7(y + 2)is 7+2 i think.
10. 8+4
11. 8+9
12. 5+12
13. 2+4
14. 6+7
15. 15-5
16. 5-3
17. 11-6
I rewrite I think if that is correct.
Byee
answer
Step-by-step explanation:
9) 7y+14
10) 32+4r
11) 8x+72
12) 12b+60
13) 8+4a
14) 42+7v
15) 15b-75
16) 15-3v
17) 66-6s
find the coordinates of F' after reflection across the line
x = -1 and then across the line
y = -1. Answer in form (a,b). Part 6a
=============================================================
Explanation:
Focus on point F only. Ignore the other points.
Point F is at (-5, -5).
The x coordinate of this point is x = -5
The horizontal distance from x = -5 to the reflection line x = -1 is 4 units. We move 4 units to the right going from x = -5 to x = -1. Move another 4 units to the right to land on x = 3
Point F = (-5, -5) reflects over x = -1 to land on point G = (3, -5) as shown in the diagram below.
Then going from point G to H has us move upward 4 units up to land on the purple line y = -1, then another 4 units up to finally arrive at point H = (3,3). This is also the location of F'.
find the coordinates of the vertices of a quadrilateral after reflection across the parallel lines; first across the x-axis and then across the line y= 1.
R(0,1), S(3,0), T(5,-4), Q(1,-3)
Answer:
R'(0, 3), S'(3, 2), T'(5, -2), Q'(1, -1)
Step-by-step explanation:
The first reflection gives you the transformation ...
(x, y) ⇒ (x, -y)
The second reflection gives you the transformation ...
(x, y) ⇒ (x, 2 -y)
Applying the second transformation to the result of the first gives the overall transformation ...
(x, y) ⇒ (x, 2 -(-y)) = (x, 2+y)
That is, the double reflection is equivalent to a translation upward of 2 units. So, we add 2 to each y-value:
R'(0, 3), S'(3, 2), T'(5, -2), Q'(1, -1)
What is the value of x in the equation 3x – one-ninthy = 18, when y = 27?
Answer:
7
Step-by-step explanation:
3x- 1/9y = 18
value of x when y is 27
3x- 1/9*27 = 18
3x- 3 = 18
3x = 18 + 3
3x = 21
x= 21/3
x = 7
Hope this helps you!
Answer:
x = 7
Step-by-step explanation:
3x-1/9(27) = 18
x = 21/3
=7
What solid 3D object is produced by rotating the rectangle about line m?
Answer:
square
Step-by-step explanation:
Answer: A tube
Step-by-step explanation:
find the equation of the parabola with the vertex at (0,0) and the focus at (-1,0)
Answer:
Step-by-step explanation:
You have to know some basics of parabolas to get this far in your math class, so hopefully you do, and what I'm about to do and say is not new or surprising to you.
If you plot the center (0, 0) which is your h and k, and then plot the focus, you should know that, since the parabola wraps itself around the focus, this parabola opens to the left. There is a work form and a standard form for a left-opening parabola. The work form will be
[tex]x=-a(y-k)^2+h[/tex] and the standard form will be
[tex]-(y-k)^2=4p(x-h)[/tex]
We will figure out what we need and will fill in both of these forms.
In general, the value of p is a distance; namely, it is the distance from the center to either the focus or the directrix (which is the same for both since the focus and the directrix are the same distance from the center, one on either side of it). From this we can determine that, since the focus is one unit away from the center, p = 1. Now that we know p we can find |a|:
[tex]|a|=\frac{1}{4p}[/tex]
Since p = 1, then [tex]|a|=\frac{1}{4}[/tex]
Now we can write the work form:
[tex]x=-\frac{1}{4}(y-0)^2+0[/tex] which of course simplifies to
[tex]x=-\frac{1}{4}y^2[/tex]
And remember we have the p value for the standard form:
[tex]-(y-0)^2=4(1)(x-0)[/tex] which simplifies a bit to
[tex]-y^2=4x[/tex] and when we solve for x:
[tex]x=-\frac{1}{4}y^2[/tex] which is the exact same as the work form!!! Look at that! : )
what is the fastest thing in the world
Answer:
The Speed Of Light
Step-by-step explanation:
help! whats the value of x
Answer:
5
Step-by-step explanation:
[tex]\dfrac{x}{x-2}=\dfrac{2x+5}{2x-1}\\\\x(2x-1)=(x-2)(2x+5)\\\\2x^2-x=2x^2+x-10\\\\2x=10\\\\x=5[/tex]
Hope this helps!
Which equation is equivalent to logx 36 = 2?
Answer:
The answer would be 36^2=x
Step-by-step explanation:
Compare these three ratios using fractions.
3 to 2 5:6 8 to 12
Think about the steps you could take to compare the ratios using fractions.
The first step is to write the ratios as fractions.
The next step is to use a to rewrite the fractions.
Finally, compare the to help you order the ratios.
Answer:
he first step is to write the ratios as fractions.
The next step is to use a
✔ common denominator
to rewrite the fractions.
Finally, compare the
✔ numerators
to help you order the ratios.
Step-by-step explanation:
1. Common denominator
2. Numerators
Find the missing part. Use an improper fraction for your answer.
Answer:
[tex]x=\frac{15}{2}[/tex] [tex]z=\frac{35113}{2703}[/tex] [tex]a=\frac{15}{4}[/tex] [tex]y=\frac{35113}{5406}[/tex] [tex]b=\frac{45}{4}[/tex]
Step-by-step explanation:
To solve this, we will have to use multiple methods, including the pythagorean theorem and the 30 60 90 rule.
In the 30 60 90 rule, it is stated that the angle opposing the side with 30 degrees is represented by [tex]s[/tex], the angle opposing the side with 60 is [tex]s\sqrt{3}[/tex] and the angle opposing 90 degree angle is represented by [tex]2s[/tex]. Looking at the whole triangle, we can see the 30, 60 and 90 degrees, and the angle with 90 has an opposing side of 15, which means we have to use 15=2s to find the other sides. When dividing 15 by 2, you get 7.5, which is s. Now we know that the angle opposing 30 is 15/2, which is x. Now that we have "s", we can also solve for z, represented by the 60 degrees. Multiply 7.5 and [tex]\sqrt{3}[/tex] to get z=35113/2703.
Now we can solve for the smaller triangles. Since we have already found x, we can use the 30 60 90 method in this too. The x (15/2) is now represented by 2s. Therefore, solve for your new s by doing this: 15/2 = 2s. You should get your 30 degree angle answer (a) with this, which is 15/4. Now that we have to use pythagorean theorem, which is [tex]a^{2} + b^{2} = c^{2}[/tex] to solve for the remaining side (y) of the small triangle. You should get 35113/5406.
Finally we have the last side left: b. Since we have so many sides now, all we have to use is the pythagorean theorem again. Use [tex]b^2+y^2=z^2[/tex] and solve for b. You should get 45/4.
FInd the distance between the points (9,3) and (1,9)
Answer:
=10
Step-by-step explanation:
1: Add the numbers
2: Factor the numbers
3: Apply radical rule
Answer: =10
Hope this helps.
Answer:
10
Step-by-step explanation:
ok
1/3 divided 8/9 I wan kno the answer
write the equation of the line passing through the given point T (-6,2) and is parallel to the line
y=2/3x
Answer:
y = [tex]\frac{2}{3}[/tex] x + 6
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = [tex]\frac{2}{3}[/tex] x ← is in slope- intercept form
with slope m = [tex]\frac{2}{3}[/tex] and c = 0
Parallel lines have equal slopes , thus
y = [tex]\frac{2}{3}[/tex] x + c ← is the partial equation
To find c substitute (- 6, 2) into the partial equation
2 = - 4 + c ⇒ c = 2 + 4 = 6
y = [tex]\frac{2}{3}[/tex] x + 6 ← equation of parallel line
solve as whole number
Answer: x < 25
Step-by-step explanation:
2/3(x+2)-1/2(x-4)>1/4(x+5)
2/3x+4/3-1/2x+2>1/4x+5/4
Multiply both sides by 12
8x+40-6x>3x+15
2x+40>3x+15
2x-3x>15-40
-x > -25
x<25
Answer:
{x:x=[[3,4,5,6...]}
Step-by-step explanation:
x∈W
[tex]\frac{2}{3}(x+2)-\frac{1}{2}(x-4)>\frac{1}{4}(x+5)\\\frac{2x+4}{3}-\frac{x+4}{2}>\frac{x+5}{4} \\\frac{2(2x+4)-3(x+4)}{2*3}>\frac{x+5}{4} \\\frac{4x+8+3x-12}{6}>\frac{x+5}{4} \\\frac{x}{y} \frac{x-4}{6}>\frac{x+5}{4}\\ 4(x-4)>6(x+5)\\ 4x-16>6x+30\\ 4x-6x>30+16\\ -2x>46\\ x<-23\\x= no solution[/tex]